The Effect of Price, Product Quality, Shipping Speed, Discount Strategy on Purchase Decisions Mediated by Word of Mouth in Micro Coffeeshop Business - Fitria Lestari PUJIASTUTI; Chablullah WIBISONO; Sajiyo SAJIYO (International Journal of Environmental, Sustainability, and Social Science, 2024)
Coffee is a very popular drink in many countries, including Indonesia. Based on data from the International Coffee Organization in 2018, Indonesia is ranked fourth as the largest coffee producer in the world. The theories used in this study are price, product quality, delivery speed, discount strategy, purchasing decision, and word of mouth. The population of this study is comprised of consumers of micro coffee shops in Batam City, 71 micro businesses in Batam City per day, namely 3905 consumers. The sample was 356 coffee shop consumers, with Slovin obtained n + 188 respondents. Discussion Resultsprice has a significant influence on the word of mouth variable, product quality does not have a significant influence on the word of variable, service speed has a significant influence on the word of mouth variable, discount strategy has a significant influence on word of mouth. Word of mouth, price, and service speed significantly influence purchasing decisions, while product quality does not. Word of mouth also effectively mediates the impact of price, product quality, service speed, and discount strategies on purchasing decisions in Batam City. The study suggests leveraging these factors to boost culinary tourism for Micro Coffeeshop businesses in Batam City.